Asymmetric Synthesis of Oxa‐Bridged Oxazocines through a Catalytic RhII/ZnII Relay [4+3] Cycloaddition Reaction. (6th November 2019) - Xu, Chaoran; Wang, Kaixuan; Li, Dawei; Lin, Lili; Feng, Xiaoming
Abstract: Oxa‐bridged oxazocines bearing three chiral carbon centers were synthesized efficiently through a bimetallic catalytic asymmetric tandem reaction of β, γ‐unsaturated α‐ketoesters with diazoimides. The process contained a rhodium‐promoted in situ generation of isomünchnone from diazoimide decomposition, and a [4+3]‐cycloaddition of β, γ‐unsaturated α‐ketoester catalyzed by a chiral N, N′ ‐dioxide‐Zn II complex. Ligand‐accelerated catalysis was found, and a possible transition‐state model was proposed to explain the origin of stereoselectivity. Abstract : Die asymmetrische Kaskadenreaktion von β, γ‐ungesättigten α‐Ketoestern und Diazoimiden wurde unter Verwendung eines bimetallischen Rhodium(II)/chiralen N, N′ ‐Dioxid‐Zink(II)‐Katalysatorsystems realisiert. Die entsprechenden oxa‐verbrückten Oxazocinprodukte mit unterschiedlichen Substituenten wurden in mittleren bis exzellenten Ausbeuten und ausgezeichneter Enantioselektivität unter milden Reaktionsbedingungen erhalten.